Kajian Produksi Ball Mill Dalam Menentukan Efektivitas Penggerusan Bijih Timah Primer Di CV Persada Tambang Intitama TK 4.218 Paku Kabupaten Bangka Selatan - Agus Cik; Mardiah Mardiah; Guskarnali Guskarnali (MINERAL, 2020)
CV Persada Tambang Intitama TK 4.218 Paku is a partner company of PT Timah Tbk, which conducts primary tin mining using the open pit method. Primary tin ore processing includes comminution, sizing, and concentration activities. Grinding using a Ball Mill is an advanced process that aims to reduce the grain size of the material in order to obtain finer grain sizes (fine material) and prepare the right grain size for the concentration process of 80 s.d - 200 mesh. In this study, the variables used are feed rate, number of Ball Mill revolutions (RPM), and water rate. The experiment was used 27 times by setting variables in combination to get effective scouring results. The material at the study site is divided into high grade and low grade materials with primary tin mineralization types in the form of stanniferous veins and gossan formed due to the oxidation process of polymetallic veins. Variable feed rate, number of Ball Mill revolutions (RPM), and water rate are very influential on the results of grinding. The higher the feed rate, the number of turns, and the rate of water the higher the Ball Mill scour, but if the variable is too high it causes overload capacity so that the output volume decreases. The effectiveness of the grinding results obtained in sample 24 with the highest production value reaching 93.9%. The effective value is obtained from setting the feed rate variable 5 to 6 Ton Per Hour (TPH), 80 rotation RPM, and water rate of 10.800 liters/hour (l/h). The result of the maximum feed rate that can be done is 9.86 TPH with LPT is 236.64 ton/day. Thus, the average LPT target of the company's 230-240 tons/day Ball Mill can be achieved